IMPLEMENTASI MODEL DISCOVERY LEARNING DENGAN PENDEKATAN TARL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA PESERTA DIDIK KELAS IX DI SMPN 1 GEGER - Maylinda Dwi Astuti; Tri Andari; Sri Hariyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to improve the mathematics learning outcomes of grade IX students at SMPN 1 Geger through the application of the Discovery Learning model combined with the Teaching at the Right Level (TaRL) approach. The main problem faced is the low understanding of mathematical concepts by students. The Discovery Learning model was chosen because it can encourage students to find concepts independently through exploration, while the TaRL approach adjusts learning to students' abilities. This study is a classroom action research conducted in two cycles, with 32 students as subjects. Data were collected through observation, interviews, and learning outcome tests, using observation sheet instruments, post-test questions, and structured interviews. The results showed a significant increase in mathematics learning outcomes. The average score in cycle I was 73.5, while in cycle II it increased to 86.8. The percentage of learning completion also increased from 56% in cycle I to 84% in cycle II. These results indicate that the application of the Discovery Learning model combined with TaRL is effective in improving the mathematics learning outcomes of grade IX students.